Value of [18F]FDG PET/CT in Diagnosis and Management of Spondylodiscitis - Lapa, Constantin; Rischpler, Christoph; Bundschuh, Ralph Alexander; Dierks, Alexander; Lang, Sigmund; Wassilew, Georgi; Alt, Volker (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
Vertebral osteomyelitis is the third most common form of osteomyelitis in patients over 50 years of age.Whereas prompt (pathogen-directed) therapy is crucially associated with better outcomes, the heterogeneous clinical presentation of disease with unspecific symptoms often delays adequate treatment initiation. Diagnosis requires a careful investigation of medical history, clinical findings and diagnostic imaging, including magnetic resonance imaging and nuclear medicine techniques.Due to its high sensitivity, [18F]FDG PET/CT is becoming increasingly important in diagnosis and management of spondylodiscitis, especially in the postoperative setting with presence of spinal hardware or other implantable devices in which MRI is limited.
Keywords: Spondylodiszitis; FDG-PET/CT; molekulare Bildgebung; Osteomyelitis; Wirbelsäule